Early exposure to parental bipolar disorder and risk of mood disorder: the Flourish Canadian prospective offspring cohort study. Issue 2 (21st October 2015) - Goodday, Sarah; Levy, Adrian; Flowerdew, Gordon; Horrocks, Julie; Grof, Paul; Ellenbogen, Mark; Duffy, Anne
Abstract: Aim: Exposure to postnatal parental depression is associated with offspring mood disorder later in life; however, little is known about exposure to parental bipolar disorder (BD) and subsequent risk of psychopathology. The aim of this study was to determine the association between the duration, severity and timing of exposure to parental BD in early childhood and subsequent risk of mood disorder. Methods: 189 offspring of a parent with BD completed annual assessments following Kiddie Schedule for Affective Disorders (KSADS) format semistructured interviews as part of an ongoing 16‐year prospective cohort study. Clinical data from the affected parents were collected over the first decade of their offspring's life using SADS‐L format semistructured interviews and coded using the Affective Morbidity Index (AMI). Results: A longer duration of exposure to parental BD was associated with a 1.5‐fold risk of any psychopathology (95% confidence interval (CI): 1.0–2.3) and a 2.5‐fold increased risk of substance use disorders (95% CI: 1.2–5.3). Exposure during the first 2 years of life was significantly associated with the risk of mood disorder (hazard ratio (HR): 1.1, 95% CI: 1.0–1.2), whereas exposure later in childhood was not. Conclusions: The duration of exposure to active parental BD in childhood is an important risk factor for the subsequent development of mood and non‐mood psychopathology risk in offspring. These findings emphasize the importance of effective treatment of parents with BD to help both themselves and their children, especially early in development.